Analysis of Superior Food Crop Comodities in Grobogan District Period 2011-2015: Analisis Komoditas Tanaman Pangan Unggulan Di Kabupaten Grobogan Tahun 2011-2015 - Azmi, Mohammad Ihsanul; Hasmarini, Maulidyah Indira (Universitas Muhammadiyah Sidoarjo, 2022)
The food crops sub-sector is the most potential and strategic sub-sector. The food crops sub-sector produces products that are staple food for most Indonesians. This study aims to determine what superior food crop commodities are owned in Grobogan Regency. The data used are food crop commodity production data in Grobogan Regency and Central Java Province in 2011-2015. The method used in this research is descriptive and quantitative analysis method using Locatioan Quotient (LQ) and Shift-Share Analysis (SSA) analysis tools. The results showed that corn, soybeans, and mung beans are the leading food crop commodities in Grobogan Regency, but rice, corn, soybeans, and cassava have faster growth than other commodities, this is indicated by the value of the proportional component that is positive, then the commodity Those that have competitiveness are rice, corn, soybeans and green beans which are indicated by the positive value of regional share growth.